Implementing the Legal Mandate of Child Protection through PUSPAGA Services: An Empirical Study on the Rights of Children Affected by Family Conflict in Tangerang City - Nur'aini; Abdullah Farooqi (Ijtimā'iyya Journal of Muslim Society Research, 2026)
Tangerang City has held Child-Friendly City status since 2017, yet violence involving children and a substantial divorce caseload show that formal recognition does not automatically secure children’s rights within families. This study examines how the Tangerang City Family Learning Center (PUSPAGA) implements the legal mandate of child protection, identifies changes experienced by child clients affected by family conflict, and analyzes constraints on service implementation. This descriptive-analytical empirical legal study combines statute, conceptual, and socio-legal approaches. The statute approach examines constitutional, international, national, ministerial, and municipal foundations of PUSPAGA services; the conceptual approach organizes children’s rights and the four general principles of the Convention on the Rights of the Child; and the socio-legal approach compares those norms with service practice. Primary data derive from semi-structured interviews with the PUSPAGA leadership, counselors, and the supervising DP3AP2KB unit. Secondary data comprise legislation, service standards, official documents, and relevant scholarship. Data were analyzed through reduction, thematic display, normative comparison, and conclusion drawing, with source and informant triangulation. PUSPAGA operationalizes the mandate through promotion, counseling and consultation, outreach, referral, and service-facilitation activities. The documented cases show three changes after intervention: cessation of self-harming behavior, restored communication between children and parents, and a stronger sense of safety. These changes correspond to the rights to life, survival and development, mental well-being, protection from violence and neglect, participation, and family care. However, preventive counseling cannot replace curative mental-health care, protection services, or legal enforcement when risks exceed PUSPAGA’s competence. PUSPAGA therefore functions as a preventive local-government mechanism that translates child-protection norms into family-level intervention. Its effectiveness depends on clearer regional institutional support, adequate professional staffing and funding, wider access, and referral coordination with schools, health and social services, protection units, religious institutions, and courts.